ESSENCE OF AND A MODEL FOR REFLECTIVE PRACTICE IN DEVELOPMENT COMMUNIATION - Pani, Prajna (PEOPLE: International Journal of Social Sciences, 2016)
A transformative approach to Integrated Development Communication framework is driving the development of and innovation in student learning with promises to significantly impact local communities. A case study concerning a themed – MBA Programme (Development Management) of a Multi-faculty State Private University in India is used to illustrate how self-learning, actionlearning and technology-enabled learning can be dynamically combined for sustainable community development. Content and topic are effectively negotiated with communities, facilitating the creation of a supportive learning and development ambience, and providing opportunities to apply new skills. The three philosophies of learning influence the program design and practice. Integrated Development Communication is introduced as an integrative construct that facilitates critical thinking, community interaction, problem solving and crossdomain learning. Learning is driven by the need to solve a problem. The paper aims to present the vision and evidences of responsible involvement in real problems to promote positive attitudes and behaviours. The paper also reflects on the essence and impact of theory of learning on integrated development communication model where Learning = Programmed Knowledge of the Past + Questioning Insight + Implementation.